Socioeconomic disparities in prehospital factors and survival after out-of-hospital cardiac arrest. Issue 8 (8th January 2021) - Møller, Sidsel; Wissenberg, Mads; Starkopf, Liis; Kragholm, Kristian; Hansen, Steen M; Ringgren, Kristian Bundgaard; Folke, Fredrik; Andersen, Julie; Malta Hansen, Carolina; Lippert, Freddy; Koeber, Lars; Gislason, Gunnar Hilmar; et al.
Abstract : Objective: It remains unknown whether patient socioeconomic factors affect interventions and survival after out-of-hospital cardiac arrest (OHCA), and whether a socioeconomic effect on bystander interventions affects survival. Therefore, this study examined patient socioeconomic disparities in prehospital factors and survival. Methods: From the Danish Cardiac Arrest Registry, patients with OHCA ≥30 years were identified, 2001–2014, and divided into quartiles of household income (highest, high, low, lowest). Associations between income and bystander cardiopulmonary resuscitation (CPR) and 30-day survival with bystander CPR as mediator were analysed by logistic regression and mediation analysis in private witnessed, public witnessed, private unwitnessed and public unwitnessed arrests, adjusted for confounders. Results: We included 21 480 patients. Highest income patients were younger, had higher education and were less comorbid relative to lowest income patients. They had higher odds for bystander CPR with the biggest difference in private unwitnessed arrests (OR 1.74, 95% CI 1.47 to 2.05). For 30-day survival, the biggest differences were in public witnessed arrests with 26.0% (95% CI 22.4% to 29.7%) higher survival in highest income compared with lowest income patients. Had bystander CPR been the same for lowest income as for highest income patients, then survival would be 25.3% (95% CI 21.5% to 29.0%) higher in highest income compared with lowest income patients, resulting in elimination of 0.79% (95% CI 0.08% to 1.50%) of the income disparity in survival. Similar trends but smaller were observed in low and high-income patients, the other three subgroups and with education instead of income. From 2002 to 2014, increases were observed in both CPR and survival in all income groups. Conclusion: Overall, lower socioeconomic status was associated with poorer prehospital factors and survival after OHCA that was not explained by patient or cardiac arrest-related factors.